AL-QUR'AN THERAPY LEARNING AND UNDERSTANDING THE TRACE OF PROPHETIC TEACHING THROUGH PROPHETIC LEADERSHIP LECTURES - Ike Gustia Ariska; Sus Budiharto (State Islamic University (UIN) Ar-Raniry, 2023)
Al-Qur'an therapy is a therapy using verses in the Al-Qur'an as a source of inspiration and media to help overcome spiritual, mental, physical and social problems. This includes reading, memorizing, understanding, living, and finding the relationship between the meaning of verses in the Koran and everyday problems and experiences. The discovery of meaning and wisdom allows students to feel emotional balance and improve their well-being, as well as being a medium for learning and understanding the traces of prophetic teachings in everyday life. An understanding of the traces of prophetic teachings was studied in the Prophetic Leadership Lecture at the Professional Psychology Study Program at the Masters Level at the Islamic University of Indonesia. One of the methods in this course is self-reflection on the four dimensions of prophetic leadership: Sidiq, Amanah, Tabligh, Fathanah. Based on self-reflection, several themes were found, namely finding new drugs, being grateful, feeling calm, and practicing knowledge. These findings enable students to become better individuals, to understand themselves and others, to function their minds and hearts through appreciating the values found in the Al-Qur'an.